Dinamika Pemilihan Kepala Pekon Di Nusawungu Kabupaten Pringsewu Tahun 2022 - Jeni Rahma; Hertanto Hertanto; Arizka Warganegara (Program Studi Ilmu Pemerintahan, Universitas Muhammadiyah Kendari, 2023)
The Pringsewu Regency Regional Regulation regarding the policy of electing Pekon Heads using the e-voting system seems rushed. With one month of preparation for the implementation of the Pekon Head election in Nusawungu village, it resulted in not being properly socialized to the community. This study describes the potential for fraud and the obstacles faced by the committee or the community in the village head election process using the e-voting system. This type of research is used qualitatively with a descriptive approach. Data collection techniques were carried out through interviews, observation, and documentation. The results of the study found that there was time and budget inefficiency in the process of implementing village head elections and the absence of the principle of Luber Jurdil (Broad, Free, Confidential, Honest, and Fair) due to the presence of the Assisting Committee in the Voting Booth who served as assistants for voters who had not or could not use the e-voting tool.